2023
DOI: 10.3389/fpls.2022.997429
|View full text |Cite
|
Sign up to set email alerts
|

AMMI and GGE biplot analyses of Bambara groundnut [Vigna subterranea (L.) Verdc.] for agronomic performances under three environmental conditions

Abstract: IntroductionThe two most common styles to analyze genotype-by-environment interaction (GEI) and estimate genotypes are additive main effects and multiplicative interaction (AMMI) and genotype + genotype × environment (GGE) biplot. Therefore, the aim of this study was to find the winning genotype(s) under three locations, as well as to investigate the nature and extent of GEI effects on Bambara groundnut production.MethodsThe experiment was carried out in the fields of three environments with 15 Bambara groundn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 41 publications
12
27
0
Order By: Relevance
“…Conversely, a deleterious interaction arises when there is a discrepancy in polarity between the genotype and the environment. The outcomes derived from our research are consistent with the findings documented 29 33 . The findings of present investigation demonstrate that the AMMI model exhibits a satisfactory level of compatibility with the collected data, thereby providing empirical justification for the application of AMMI 2.…”
Section: Resultssupporting
confidence: 88%
“…Conversely, a deleterious interaction arises when there is a discrepancy in polarity between the genotype and the environment. The outcomes derived from our research are consistent with the findings documented 29 33 . The findings of present investigation demonstrate that the AMMI model exhibits a satisfactory level of compatibility with the collected data, thereby providing empirical justification for the application of AMMI 2.…”
Section: Resultssupporting
confidence: 88%
“…( 2023 ), Esan et al. ( 2023 ), and Kindie et al. ( 2022 ), who reported on dividing testing environments into various mega environments with different sectors and numbers of genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The AMMI model generates AMMI1 and AMMI2 biplots for evaluating the significant multiplicative interactions of agronomic traits between genotypes and environments in multi-environment field trials. AMMI1 biplot gives visual information on yield potential and stability performance of genotypes under evaluation ( Esan et al., 2023 ). In the AMMI1 biplot the ordinate and abscissa axes stand for the influence of environment effects and the mean yields, respectively ( Olivoto et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the AMMI1 biplot the ordinate and abscissa axes stand for the influence of environment effects and the mean yields, respectively ( Olivoto et al., 2019 ). Esan et al. (2023) and Habtegebriel (2022) reported that genotypes located on the right side of the origin of the biplot along the abscissa axe had greater yields whereas those on the left side had lower yields, and that the influences of environments are larger when genotypes are arranged farther from the abscissa axe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation